16. CORRELATION BETWEEN NUMBER OF CHROMOSOMES ALTERATIONS AND TIME-LAPSE EMBRYO SCORE: PRELIMINARY OUTCOMES. (August 2019) - Gomes, A.; Martin, H.; Fugii, M.; Gazeto, B.; Conatti, M.; Bonetti, T.; Riboldi, M.; Monteleone, P.
Abstract : Introduction: Despite of conventional morphological evaluation is the classical method for embryo selection it clearly has limitations. Recently, time-lapse monitoring allows the embryo quality classification based on morphokinetics. Moreover, Preimplantation Genetic Test for Aneuploidy (PGT-A) is applied to investigate the genetic status of the embryos and the selection of euploid embryos for transfer is supposed to lead to improved clinical outcomes. The association of morphokinetics and PGT-A opened new opportunities to refine blastocyst selection. However, knowledge of the impact of chromosome alterations on embryo morphokinetics need to be increased. The aim of this study was to correlate embryo score from time-lapse imaging with chromosome status of the embryos evaluated by PGT-A. Material & methods: This is a preliminary retrospective cohort study of prospectively collected data for 81 ICSI cycles performed at a private assisted reproduction center in Brazil, between April and November 2018. A total of 260 embryos developed into blastocysts suitable for biopsy and were analyzed in this study. Embryos were cultured in the Embryoscope® time-lapse imaging chamber (Vitrolife®) and the image acquisition system was set to capture images from each embryo every 15 minutes during the entire culture interval. Embryos were scored from zero to 10 based on the timings of cell divisions with the start of ICSI until the blastocyst formation and expansion on day 5 or 6 of development. PGT-A was elective, but strongly encouraged for patient's ≥37 years old, implantation failure, recurrent miscarriage or severe male factor cases. Embryos were biopsied at a blastocyst stage and PGT-A was carried out at a global reference laboratory (Igenomix Brasil) through NGS. Results: The women age varied from 25 to 42 years (38.5±2.9) and 1 to 10 blastocysts were biopsied per patient (3.2±2.0). Of the 260 biopsied blastocyst, 38.7% were euploid. The embryos scores were slightly lower in aneuploid (5.9±2.1) than euploid (6.4±2.1) blastocysts with a marginally significant statistical difference (p=0.067). The number of altered chromosomes were annotated and inversely correlated to embryo score (Pearson correlation: r=-0.210; p=0.001). Then we classified the number of altered chromosomes as none (euploid), 1-2, 3-6 and more than 6 (chaotic). We only observed a significant difference between the time-lapse embryo score of chaotic (3.9±1.3) and euploid (6.4±2.1; p=0.026) blastocysts. The 1-2 (6.1±2.0) or 3-6 (5.4±2.3) alterations showed similar time-lapse embryo score to euploid embryos (p=1.000 and p=0.161, respectively). The multivariate linear regression model have confirmed the higher number of altered chromosomes lower the time-lapse embryo score (Coef=-0.149; p=0.026) adjusted for confounders as women age and time of culture. Conclusions: The findings of our study suggest the number of altered chromosomes affect the embryo morphokinetics, leading to a reducing time-lapse embryo score. Although there seems to be a relationship between the ploidy status and complexity of chromosome alterations with the embryo morphokinetics, time-lapse embryo score is not enough to predict chromosome alterations, and therefore, replace PGT-A. These are preliminary outcomes and further studies are being conducted to investigate the association of chromosome alterations with embryo morphokinetics and relate them with clinical outcomes.